Heroic Telengana: reminiscences & experiences - Nārāyaṇareḍḍi, Rāvi (Communist Party publication, 1973)
Reminiscences of a freedom fighter and political leader about the armed struggle in the Telengana region of Andhra Pradesh, 1946-51.